Testosterone Therapy and Cardiovascular Risk: A Critical Analysis of Studies Reporting Increased Risk. Issue 1 (11th December 2020) - Khera, Mohit; Miner, Martin; Jaffe, Jonathan; Pastuszak, Alexander W.
ABSTRACT: Background: Treatment of "adult-onset hypogonadism" (AOH) with exogenous testosterone therapy (TTh) to raise serum testosterone (T) levels may influence cardiovascular (CV) risk factors in patients with AOH, whereas low endogenous T levels are associated with an increased CV risk and mortality. Aim: To critically evaluate studies reporting increased CV risk associated with TTh and to provide an overview of the risks and benefits of restoring T levels through exogenous TTh. Methods: A review of publications focusing on the association between TTh and increased CV risk was conducted, and the study methodologies and conclusions of each were critically evaluated. Further, recent clinical and epidemiological studies associating AOH or TTh with a change in CV risk, and pertinent hematologic and vascular effects noted in animal studies and in vitro, as well as in clinical practice were also reviewed. Outcomes: A review of the literature shows that untreated testosterone deficiency and/or low T is associated with an increase in CV risk and adverse outcomes, with numerous studies and meta-analyses to support a positive association between exogenous TTh and an improvement in CV risk factors in men with AOH. RESULTS: Numerous studies in the literature demonstrate the positive benefits of using TTh; however, since 2013, some publications have suggested a link to increased CV risk associated with TTh. A number of these studies retrospectively analyzed insurance claims databases using diagnosis codes, procedures codes, and prescription information. Many reviews published since have pointed out the methodological flaws and debatable conclusions of these studies. Clinical Implications: A careful assessment of the patient's current health status and CV risk factors should be weighed against the benefits and possible risks resulting from TTh, and consideration should be given to deferring treatment pending resolution or stabilization of CV disease or risk factors. Strengths & Limitations: In this review, we provide an in-depth analysis of studies reporting increased CV risk with TTh. Many of the studies were not well-designed, randomized, double-blind, prospective clinical trials but rather post hoc analyses of cohort data. These studies may reflect bias in how treatment and nontreatment decisions are made or reflect conclusions based on widely cited methodological flaws. CONCLUSION: Appropriate patient selection supported by low pre-treatment T levels and monitoring T levels during treatment with the goal of achieving and maintaining physiologic levels all contribute to the safe and effective use of TTh in men with AOH.